Optimization of process parameters for the production of polypropylene ternary nanocomposites - Muyibi, Suleyman Aremu; Yusof, Faridah; Al-Khatib, Ma'an Fahmi Rashid; Shah, Qasim Hussain; Olalekan, Salawudeen Taofeeq (2011)
Preparation of Polypropylene ternary nanocomposites was accomplished by blending multiwall carbon nanotube (MWCNT) in polypropylene/clay binary system using melt intercalation method. The effects of MWCNT loadings (A), melting temperature (B) and mixing speed (C) were investigated and optimized using center composite design. The analysis of the fitted cubic model clearly indicated that A and B are the main factors influencing the tensile properties at a fixed value of C. However, the analysis of variance showed that the interactions between the process parameters such as; AB, AC, AB2, A2B and ABC are highly significant in both tensile strength and Young’s modulus enhancement while no interaction is significant in all models considered for elongation. The established optimal conditions gave 0.17%, 165OC, and 120rpm for A, B and C respectively. These conditions yielded a percentage increase of 57 and 63% for tensile strength and Young’s modulus respectively compared to the virgin Polypropylene used.